Investor’s Perception with Respect to Corporate Governance: A Study of Selected IT firms - Kumar, Ramesh (Integrated Journal for Research in Arts and Humanities, 2024)
This research delves into the complexities of corporate governance within the Indian IT sector, focusing on the perspectives and awareness levels of retail investors. It explores the evolution of corporate governance practices, influenced by global trends and local market dynamics, in leading IT companies such as Infosys, Wipro, and TCS. The study employs a comprehensive survey to assess the demographic profile, investment patterns, and corporate governance awareness among IT professionals in the Delhi NCR region. The findings reveal a youthful demographic with a cautious investment approach and varying degrees of engagement with corporate governance issues. Notably, a strong relationship is observed between professional roles and the understanding of corporate governance norms, particularly Clause 49 of the Listing Agreement. The study underscores the importance of corporate governance awareness in shaping investment decisions and highlights the need for transparent and accountable governance practices to align with investor expectations. It contributes valuable insights to the discourse on corporate governance in Indian IT firms, providing a foundation for enhancing investor-friendly governance frameworks.